7-3x-(-5x+2)+1+7x=5x

Simple and best practice solution for 7-3x-(-5x+2)+1+7x=5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7-3x-(-5x+2)+1+7x=5x equation:


Simplifying
7 + -3x + -1(-5x + 2) + 1 + 7x = 5x

Reorder the terms:
7 + -3x + -1(2 + -5x) + 1 + 7x = 5x
7 + -3x + (2 * -1 + -5x * -1) + 1 + 7x = 5x
7 + -3x + (-2 + 5x) + 1 + 7x = 5x

Reorder the terms:
7 + -2 + 1 + -3x + 5x + 7x = 5x

Combine like terms: 7 + -2 = 5
5 + 1 + -3x + 5x + 7x = 5x

Combine like terms: 5 + 1 = 6
6 + -3x + 5x + 7x = 5x

Combine like terms: -3x + 5x = 2x
6 + 2x + 7x = 5x

Combine like terms: 2x + 7x = 9x
6 + 9x = 5x

Solving
6 + 9x = 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
6 + 9x + -5x = 5x + -5x

Combine like terms: 9x + -5x = 4x
6 + 4x = 5x + -5x

Combine like terms: 5x + -5x = 0
6 + 4x = 0

Add '-6' to each side of the equation.
6 + -6 + 4x = 0 + -6

Combine like terms: 6 + -6 = 0
0 + 4x = 0 + -6
4x = 0 + -6

Combine like terms: 0 + -6 = -6
4x = -6

Divide each side by '4'.
x = -1.5

Simplifying
x = -1.5

See similar equations:

| 2x+4x-9x+7= | | 5(20x+25)=925 | | 10*xy+90=72x | | 12y-5y-7+4= | | 10x-50=7x+1 | | x-(5-2x)=1+(2+x) | | 2+(-3)(4)-(-5)= | | 15=-7+44y | | -100=x^2-29x | | 10x=1+5x | | 14+12y=16+9y | | .25x+9=1 | | 28-7x=-28x-28 | | X-13.6=-16 | | 12x-42+3x=6(3x-9) | | -23+13n+47-5n=-28 | | 5.3+(w+1.2)= | | -2u+1.4=-0.6 | | 10x=5+1x | | -2(b+7)=3b+7-5b | | H=-16t^2+7t+28 | | 8x+5x+8+6= | | 8-1-(18-2)/8= | | X-2y=3z | | 31-(2x+3)=2(x+4)+x | | 90+x*86=45x+8 | | -5(w+3)=-7w-35 | | -20-f=20-6f+20 | | 7(2x-1)=-3(5x-3) | | 3x+2(-6+2)=-86 | | 12x+y=60 | | m^2+11m+28=0 |

Equations solver categories